2017
DOI: 10.3892/mmr.2017.6379
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of serum manganese levels in an Italian population

Abstract: Manganese (Mn) is both essential and toxic for humans, mainly depending on the total levels and its species. Main sources of exposure include food and air pollution, particularly motorized traffic. We sought to determine the potential influence of these sources on serum total levels of Mn and Mn species. We selected a random sample of municipality residents from an Italian urban municipality, from whom we collected detailed personal information, dietary habits and a blood sample for serum Mn determination. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…Food pattern modeling has been used to estimate community level nutrient intake through modeling methods like the present approach elsewhere [ 29 , 30 , 31 , 32 ]. However, this is the first study, to our knowledge, that has compared the effectiveness of food pattern modeling to repeated multiple-pass memory-based dietary assessment by comparing acute and chronic measurements of nutrient status by hematological outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food pattern modeling has been used to estimate community level nutrient intake through modeling methods like the present approach elsewhere [ 29 , 30 , 31 , 32 ]. However, this is the first study, to our knowledge, that has compared the effectiveness of food pattern modeling to repeated multiple-pass memory-based dietary assessment by comparing acute and chronic measurements of nutrient status by hematological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its definition in the Dietary Guidelines for Americans [ 2 ], there is no standardized approach to food pattern modeling as a form of dietary or nutrient assessment. In addition to the methodology from the present study, other studies reviewed suggested a variety of models and methods that were employed with characteristics that met the definition of food pattern modeling [ 3 , 4 , 6 , 7 , 8 , 30 , 31 , 32 ]. To use food pattern modeling broadly, methodology and further validation should be considered for research and programming moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…The limit of quantification of the determination method was 18 ng/L related to native serum. Regular laboratory intercomparing studies (GEQUAS quality controls scheme and IRMM/EU certification campaign) as well as regular analysis of certificate material, namely ERM-BD-150 (skimmed milk powder from European Reference Materials-BD150), ERM-CD281 (rye grass from European Reference Materials-CD281), and Recipe RM ClinCal Plasma, were implemented for quality control [24][25][26]. The selection of CRMs was adopted according to sample matrix (e.g., plasma RM from Recipe Chemicals + Instruments GmbH, Munich, Germany) and to comparable (low) concentrations to samples (e.g., Cd in CRM CD281 or ERM-BD-150).…”
Section: Laboratory Analysismentioning
confidence: 99%
“…Sensitivity analyses adding smoking habits (coded as 0, 1 and 2 for never, former and current smokers, respectively) and BMI were tested. Finally, the environmental source of Se through air was tested using levels of particulate matter <10 µm (PM 10 ) estimated with a methodology previously reported for other trace elements [i.e., cadmium (28) and manganese in this issue (41)].…”
Section: Laboratory Analysismentioning
confidence: 99%